Diastolic Dysfunction of Hypertrophic Cardiomyopathy Genotype‐Positive Subjects Without Hypertrophy Is Detected by Tissue Doppler Imaging: A Systematic Review and Meta‐analysis. (6th June 2017) - Liu, Wen; Sun, Dandan; Yang, Jun
Abstract : Objectives: To evaluate whether diastolic dysfunction derived by tissue Doppler imaging (TDI) would be an earlier manifestation in genotype‐positive hypertrophic cardiomyopathy (HCM) subjects without left ventricular hypertrophy (LVH). Methods: We systematically searched Pubmed, Medline, and Web of Science with an upper date limit of June 2016 for studies evaluating the diastolic function of HCM genotype‐positive subjects without hypertrophy (G+/LVH−). Based on the inclusion criteria, eligible studies were selected. The quality of selected studies was assessed by the Newcastle–Ottawa Scale before being included in the meta‐analysis. The statistic data such as weighted mean difference (WMD) and 95% confidence interval (CI) were calculated by Stata 12.0 software. Results: Seventeen studies were included in the systematic review, and 12 were finally involved in the meta‐analysis. The G+/LVH− subjects showed decreased Ea derived by TDI on both the interventricular septum (WMD [95% CI] = –1.822 [–3.104, –0.541]) and lateral wall (WMD [95% CI] = –2.269 [–3.820, –0.719]), and increased E/Ea on both interventricular septum (WMD [95% CI] = 1.363 [0.552, 2.174]) and lateral (WMD [95% CI] = 1.339 [0.386, 2.293]) wall. Conclusions: Tissue Doppler imaging–derived diastolic dysfunction can be found in HCM genotype‐positive subjects without hypertrophy.